Karakteristik Kimia dan Kesukaan Snack Bar Berbahan Tepung Uwi Ungu dan Tepung Komposit - Putri, Renata M; Tamaroh, Siti; Yulianto, Wisnu A (AGRITEKNO: Jurnal Teknologi Pertanian, 2024)
In the production snack bars, local food ingredients such as corn flour, red bean flour, and purple yam flour are required. This research has the objective to determine and examine the comparison between corn flour, red bean flour, and purple yam flour that is ideal for meeting the preferences of the panelist, as well as the physical and chemical requirement, and the level of acceptance of the sack bars. A Completely Randomized Design is employed with two components and two replications. The first factor being examined is the ratio of corn flour to red bean flour, specifically (90%:5%), (90%:10%), and (85%:15%). The second factor is the addition of purple yam flour (20%, 30%, and 40% of the total flour used 100%). The snack bars undergo physical tests to evaluate their texture and color. In addition to evaluating the acceptability of the snack bars, chemical analysis is conducted to determine the levels of anthocyanins, antioxidant activity, moisture content, ash, protein, fat, and crude fiber. Color, texture, antioxidant activity, and the level of preference among panelists are significantly influenced by the proportion of corn flour and red bean flour in conjunction with the added purple yam flour. The most preferred treatment of the snack bar consists of 85% corn flour, 15% red bean flour, and 40% purple yam flour. This snack bar has the following nutritional values: 12.75 (% db) ash, 5.11 (% db) protein, 17.94 (% db) fat, 10,93 (% db) crude fiber, and 13,22 mg/100 g (db)of anthocyanins.